Diverse stone artefacts around Lake Woods, Central Northern Territory, Australia. Issue 2 (4th May 2021) - Shipton, Ceri; Cohen, Tim; Forbes, Matthew; Boesl, Fabian; Jacobs, Zenobia; Dixon, Raymond Dimakarri; Dixon, Eleanor; Kingston, Susan; Albert, Claudette; O'Connor, Sue
Abstract: Lake Woods is a large freshwater body on the northern edge of Australia's arid zone where research since the late 1960s has suggested late Pleistocene, later Holocene, and recent human occupations. We report on surface collections and test excavations undertaken at four sites on the western side of the lake basin in 2019. Each site produced a distinctive lithic assemblage, characterised by different types of shaped and retouched lithics and grindstones. Some material matches the ethnographic descriptions of W. Murgatroyd and R. Paton of local stone tool technology. Our work also confirms the hypothesis of M. Smith that there was later Holocene occupation in the area; and is not inconsistent with the hypothesis of J. Bowler that there was a late Pleistocene occupation around the lake, but definitive evidence of this remains ambiguous. Grindstones occur at all sites, indicating that the harvesting of grass seeds was consistently an important subsistence component for people living by the lake. Distinctive lithic types are found at Lake Woods that are characteristic either of tropical northern Australia or arid southern Australia, suggesting the lake was an inter-regional locus for human activity and a potential zone of interaction between different groups at various times in the past.